Examination on determinants of customer satisfaction in student food services - Mohd. Wazir, Muhammad Zafir (2017)
Customer satisfaction plays a pivotal role in success of every business organization whether it is meant for a product or a service. The increasing numbers of higher education students on university campuses ensured the expansion of demand for food service availability and quality on campus. This research conducted to examine impact of service quality, food quality, price, ambience and sustainability practices on customer satisfaction in student's food services. This study also will analyze the mediating effect of perceived value between service quality, food quality, price, ambience, sustainability practices and customer satisfaction. Questionnaires had distributed to 310 respondents which are students who experienced dine at sustainability cafeterias in UTM Skudai. Finding of this study shows that service quality, food quality and sustainability practices positively impact customer satisfaction. Finding also indicated that food quality, ambience, sustainability practices positively impact on perceived value. In addition, results indicated that perceived value mediate relationship between service quality, food quality, and ambience and sustainability practices with customer's satisfaction as independent variable. Practical implication of this study can be utilized by food service to improve customer satisfaction efficiently.